Geriatric distal femur fracture: Are we underestimating the rate of local and systemic complications?. Issue 8 (August 2016) - Moloney, Gele B.; Pan, Tiffany; Van Eck, Carola F.; Patel, Devan; Tarkin, Ivan
Abstract: Background: Low energy distal femur fractures often occur in a fragile elderly population that is prone to local and systemic complications following operative treatment of extremity fractures. The nonunion rate and early complication rate following laterally based locked plating in this specific fracture are not well described. Methods: We conducted a retrospective cohort study conducted at three affiliated tertiary care hospitals to evaluate nonunion, early post operative complications, discharge disposition, length of stay, and mortality in patients over 60 years old undergoing laterally based locked plating of a low energy distal femur fracture. Results: Forty-four out of 176 patients were deceased at one year (25%). Predictors of one year mortality included older age, higher Charlson Comorbidity Index (CCI), and delay to surgery greater than 2 days (p < 0.001). Of 99 patients alive and with follow up at one year, 24 (24%) developed a nonunion and 21 of 24 required nonunion surgery. Development of a surgical site infection was statistically significantly correlated with development of nonunion. Age and CCI did not predict development of nonunion. Average length of stay was 10 days and 82% of patients were discharged to a skilled nursing facility. Thirty eight percent of patients experienced at least one postoperative systemic complication. Conclusions: Laterally based locked plating of the low energy geriatric distal femur fracture is most often followed by a tumultuous post-operative course with a high rate of local and systemic complications including death, nonunion, and extended hospital stays. Level of evidence: Level III prognostic.